Parental factors affecting deaf students' performance in the English subject - Baldago, Rainna Melisa R. (2009)
Parents' mode of communication, educational attainment and parental involvement are factors that influence the performance of high school students who are severely to profoundly deaf in a deaf high school in Iloilo City. A questionnaire was administered to the parents to identify their mode of communication, educational attainment and level of involvement. An interview with the deaf students was also administered. 15 respondents were identified having signing parents and 19 who hae non-signing parents. Deaf students' performance was generally unsatisfactory. Statistical results showed that only parental involvement had a relationship with the performance of the deaf student, albeit low. In contracts, interviews with the deaf students showed it was important that parents were able to use sign language in communicating with them.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Special education -- Parent participation -- Philippines -- Iloilo City; Parents of children with disabilities -- Philippines -- Iloilo City; English language -- Study and teaching (Secondary) -- Philippines -- Iloilo City; Deaf children -- Means of communication -- Philippines -- Iloilo City; Deaf children -- Education -- Philippines -- Iloilo City; High school students -- Rating of -- Philippines -- Iloilo City